Evidence for spinal disinhibition as a pain-generating mechanism in fibromyalgia syndrome - Anne Marshall; Jamie Burgess; Andreas Goebel; Bernhard Frank; Uazman Alam; Andrew Marshall (PAIN Reports)
Abstract. Introduction:. Pain phenomenology in patients with fibromyalgia syndrome (FMS) shows considerable overlap with neuropathic pain. Altered neural processing leading to symptoms of neuropathic pain can occur at the level of the spinal cord, and 1 potential mechanism is spinal disinhibition. A biomarker of spinal disinhibition is impaired H-reflex rate-dependent depression (HRDD). Objectives:. This study investigated whether patients with FMS exhibit evidence of spinal disinhibition. Methods:. Thirty-one individuals with FMS and 20 healthy volunteers underwent testing of Hoffman reflex including HRDD, along with assessment of clinical signs and symptoms, pressure pain thresholds, temporal summation of pain (wind-up), and conditioned pain modulation (CPM). Small nerve fibre structure was quantified using intraepidermal nerve fibre density and corneal confocal microscopy. Results:. Patients with FMS had significantly impaired HRDD at 1 Hz (P = 0.026) and 3 Hz (P = 0.011) and greater wind-up ratio (P = 0.008) compared with healthy controls. Patients with the most impaired HRDD also had the most inefficient CPM but HRDD was not associated with wind-up. Both HRDD and CPM were most impaired in patients with a shorter duration of disease. Conclusion:. We demonstrate for the first time that people with FMS show evidence of spinal disinhibition, which is most dominant in shorter duration of disease and may represent a putative mechanism of pain generation in FMS. Identifying people with impairment of central pain processing at an early stage may provide opportunities for targeted mechanistically directed interventions. Longitudinal studies are warranted to tease out the precise contribution of these mechanisms.